2018
DOI: 10.1016/j.neuroimage.2018.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain connectivity is predictable from anatomic network's Laplacian eigen-structure

Abstract: How structural connectivity (SC) gives rise to functional connectivity (FC) is not fully understood. Here we mathematically derive a simple relationship between SC measured from diffusion tensor imaging, and FC from resting state fMRI. We establish that SC and FC are related via (structural) Laplacian spectra, whereby FC and SC share eigenvectors and their eigenvalues are exponentially related. This gives, for the first time, a simple and analytical relationship between the graph spectra of structural and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
196
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 133 publications
(206 citation statements)
references
References 54 publications
(80 reference statements)
5
196
1
Order By: Relevance
“…These eigen-relationships arise naturally from a biophysical abstraction of fine-scaled and complex brain activity into a simple linear model of how mutual dynamic influences or perturbations can spread within the underlying structural brain network, a notion that was advocated previously 30,42,43 . We had previously reported that the brain network Laplacian can be decomposed into its constituent "eigenmodes", which play an important role in both healthy brain function 30,31,[44][45][46] and pathophysiology of disease 44,[47][48][49] .…”
Section: A Hierarchical Analytic Low-dimensional and Linear Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…These eigen-relationships arise naturally from a biophysical abstraction of fine-scaled and complex brain activity into a simple linear model of how mutual dynamic influences or perturbations can spread within the underlying structural brain network, a notion that was advocated previously 30,42,43 . We had previously reported that the brain network Laplacian can be decomposed into its constituent "eigenmodes", which play an important role in both healthy brain function 30,31,[44][45][46] and pathophysiology of disease 44,[47][48][49] .…”
Section: A Hierarchical Analytic Low-dimensional and Linear Spectramentioning
confidence: 99%
“…At this scale, graph theory involving network statistics can phenomenologically capture structure-function relationships [23][24][25] , but do not explicitly embody any details about neural physiology 14,15 . Strong correlations between functional and structural connections have also been observed at this scale 3,[26][27][28][29][30][31][32] , and important graph properties are shared by both SC and functional connectivity (FC) networks, such as small worldness, power-law degree distribution, hierarchy, modularity, and highly connected hubs 24,33 .…”
Section: Introduction the Structure-function Problem In Neurosciencementioning
confidence: 99%
“…Some of the main goals in joint structure–function modeling are to increase the accuracy of noisy connectivity measurements, identify function‐specific subnetworks (Chu, Parhi, & Lenglet, ) or to predict one modality from the other (Honey et al, ). One recent publication with the goal of predicting function from structure used the network diffusion (ND) model (Abdelnour, Dayan, Devinsky, Thesen, & Raj, ; Abdelnour, Voss, & Raj, ), which assumes functional activation diffuses along white matter connections. This model is linear, has a simple, closed‐form solution and only one tuning parameter, making it computationally more tractable and less prone to overfitting than, for example, high‐dimensional, nonlinear neural mass models.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the main goals in joint structurefunction modeling are to increase the accuracy of noisy connectivity measurements, identify function-specific subnetworks or to predict one modality from the other (Honey et al, 2009). One recent publication with the goal of predicting function from structure used the network diffusion (ND) model (Abdelnour, Dayan, Devinsky, Thesen, & Raj, 2018;Abdelnour, Voss, & Raj, 2014), which assumes functional activation diffuses along white matter connections.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how flexible macroscopic functional architecture arises from the stable scaffold of anatomical white matter fiber tracts in the brain is a major field of inquiry in neuroscience. This has been investigated via the relationship between structural and functional connectivity (SC and FC, respectively) between brain regions in fMRI and MEG (Abdelnour, Dayan, Devinsky, Thesen, & Raj, 2018;Atasoy, Donnelly, & Pearson, 2016;Cabral et al, 2014;Damoiseaux & Greicius, 2009;Deco et al, 2013;Glomb, Ponce-Alvarez, Gilson, Ritter, & Deco, 2017;Goñi et al, 2014;Hagmann et al, 2008;Honey et al, 2009;Meier et al, 2016;Tewarie et al, 2019Tewarie et al, , 2014Vincent et al, 2007) . Concurring findings from these studies show that FC between regions of interest (ROIs)/sources located in the gray matter is in part shaped by anatomical connections of the SC, such that the strength of SC (fiber count, density) is predictive to some degree of the strength of FC (correlation, coherence, etc.)…”
Section: Introductionmentioning
confidence: 99%